#Digital Culture: Reflections on Contemporary Political Consumption - Taricco, Lucrecia (2020)
In everyday life context, inscribed in the cultural battlefield of the material and symbolic (hyper)mediations of the Internet, we are interested in critically reflecting on the approach to cultural practices of digital consumption. Inside the political communication field, we observe that today multiple phenomena are embedded in the daily configuration of these practices, which lead us to rethink the role of traditional audience measurements and statistics, to the use of big data and algorithms, different political-cultural outlooks of audiences, challenged by a global crisis in the subject of cybersecurity. Among other conditions of going digital, we will thus understand such contemporary consumption as an issue concerning political power, taking into account its ideological dimension.